Improving Children's Creativity through Outdoor Learning Jumputan Batik Activities - Sulistyowati, Raya; Syafitri, Novi; Rakhmawati, Dwi Yuli; Aini, Lazimah Nur; Izzahtus, Siska; Brilianita, Setia; Andhini, Surya (Universitas Negeri Surabaya, 2023)
Jumputan batik is batik made using tie and dye techniques using the desired color. The cloth used for batik is tied with a thick rope or rubber to prevent the color from entering the cloth and forming the desired motif. This jumputan batik activity was carried out at SDN 2 Kauman which coincides in Nganjuk Regency which aims to explain the importance of introducing jumputan batik art to elementary school children, and also to train students' creativity which is shown by the results of the creation of tie and coloring of each batik they produce. The method used in this activity is the practical method. The results produced in outdoor learning activities by holding jumputan batik for students at SDN 2 Kauman are that students gain product-making skills and new knowledge about jumputan batik which can be obtained through this activity and understand how jumputan batik techniques and understand the tools and materials needed to make jumpy batik. Keywords: jumputan batik, creativity, student